2012
DOI: 10.1111/j.1752-4571.2012.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and risks of introgression in the wild Coffea arabica gene pool in south‐western Ethiopian montane rainforests

Abstract: The montane rainforests of SW Ethiopia are the primary centre of diversity of Coffea arabica and the origin of all Arabica coffee cultivated worldwide. This wild gene pool is potentially threatened by forest fragmentation and degradation, and by introgressive hybridization with locally improved coffee varieties. We genotyped 703 coffee shrubs from unmanaged and managed coffee populations, using 24 microsatellite loci. Additionally, we genotyped 90 individuals representing 23 Ethiopian cultivars resistant to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 70 publications
(149 reference statements)
1
87
0
1
Order By: Relevance
“…diversity using diverse groups of materials such as cultivar, mutants, spontaneous/subspontaneous accessions (terms defined in Charrier and Eskes 2004) and hybrids as well as different marker systems (Aerts et al 2012;Aga et al 2003;Dessalegn et al 2008b). These studies indicated a limited genetic variability available for arabica breeding programs, even with the wild accessions (Aga et al 2003;Anthony et al 2001;WCR 2014).…”
Section: Communicated By a M Dandekarmentioning
confidence: 99%
“…diversity using diverse groups of materials such as cultivar, mutants, spontaneous/subspontaneous accessions (terms defined in Charrier and Eskes 2004) and hybrids as well as different marker systems (Aerts et al 2012;Aga et al 2003;Dessalegn et al 2008b). These studies indicated a limited genetic variability available for arabica breeding programs, even with the wild accessions (Aga et al 2003;Anthony et al 2001;WCR 2014).…”
Section: Communicated By a M Dandekarmentioning
confidence: 99%
“…Coffee density is high because of the planting of local cultivars between the wild coffee individuals. Local cultivars did not result from rigorous breeding, however, and still represent very high genetic diversity (Aerts et al, 2012). Soil disturbance is high, and mulching and slashing of the herbaceous undergrowth is common.…”
Section: Study Sites and Samplingmentioning
confidence: 99%
“…Usually the template matching algorithm is used to identify the circuit breaker character: the character feature extraction and image (template edge feature, SIFT feature), by matching to find the relationship between the feature points, to determine the template matching window; or the use of the template and the image to be recognized the relativity of gray value, for in the image of the template may position. Metric function common to have absolute difference (Sum of Absolute Differences:SAD) [3], (Sum of Squared Difference: square SSD) [4], the normalized cross correlation (Normalized Cross Correlation: NCC) [5].…”
Section: Introductionmentioning
confidence: 99%